Psychological Wellbeing in Global Educational Settings: Exploring the Intersection of Gender and Disability - Karimah, Rinda Nurul; Robin, Dwi Merry Christmarini (P3M Politeknik Negeri Jember, 2024)
This literature review examines the intersection of psychological wellbeing with gender and disability within educational contexts worldwide. Psychological wellbeing is a critical factor influencing students' academic performance and overall life satisfaction. This review investigates current research on how gender and disability impact psychological wellbeing in educational settings, highlighting the unique challenges and supports required for diverse student populations. Findings reveal that gender-specific issues, such as societal expectations and stereotypes, significantly affect students' mental health. Similarly, students with disabilities face compounded challenges including stigma, social isolation, and inadequate support, which intersect with gender-related concerns. The review shows the importance of tailored interventions and inclusive policies that address these intersectional issues to foster a supportive educational environment. Recommendations include enhancing educator awareness, promoting equity in support systems, and developing targeted mental health resources. By integrating insights from gender and disability perspectives, this review provides a comprehensive understanding of the factors influencing psychological wellbeing and emphasizes the need for an inclusive approach to support all students effectively.